Hubungan antara minat dan motivasi belajar dengan hasil belajar kognitif matematika materi geometri di SD - Vita Sulistya; Jenny Indrastoeti Siti Poerwanti; Sularmi Sularmi (Didaktika Dwija Indria, 2022)
This study aims to 1) describe whether there is a relationship between interest and cognitive learning outcomes in geometry for fifth-grade elementary school students, 2) describe whether there is a relationship between motivation and cognitive learning outcomes in geometry for fifth grade elementary school students, 3) describe whether there is a relationship between interest and motivation to learn together with the cognitive learning outcomes in geometry material for fifth-grade elementary school students. This research includes quantitative correlation research with an ex post facto approach. The population of this study were students of class V SD in Garung District, Wonosobo in the academic year 2021/2022. The sample was taken using the Probability Sampling technique. Data collection techniques using tests and questionnaires. Based on the analysis of research data, it can be concluded that 1) There is a positive and significant relationship between interest and cognitive learning outcomes in geometry, 2) There is a positive and significant relationship between motivation and cognitive learning outcomes in geometry, 3) There is a positive and significant relationship between interest and motivation to learn together with the cognitive learning outcomes in geometry. These relationships have a strong degree of correlation.